Analysis Persuasive Sentences Advertisement Shopee on Youtube - Gumelar, Surya; Dian Hartati; Sinta Rosalina (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study focuses on analyzing persuasive sentences used in Shopee advertisements on YouTube. This study describes the results of analyzing persuasive sentences in Shopee advertisements. This study is based on the structure of persuasive sentences, namely Introduction to the Issue, Series of Arguments, Call to Action, and Reaffirmation, so that the influence of the advertisements presented by Shopee will be clearly seen. This type of research uses a qualitative descriptive method. The data collection technique in this study uses the observation and note-taking technique, The researcher observed Shopee advertisements on YouTube published between January and December 2024 that contained persuasive sentences. After conducting the observation, the researcher found five advertisements that contained persuasive sentences in accordance with the persuasive sentence structure. by watching Shopee advertisements on YouTube and then noting the sentences used by Shopee advertisements. The data analysis technique in this study uses three stages: data reduction, data presentation, and conclusion. The results of this study show that four Shopee advertisements meet the persuasive sentence structure. This study uses five Shopee advertising videos as data for the use of persuasive sentences in Shopee advertisements in accordance with the structure of persuasive sentences. These Shopee advertisements are long enough to explain the message thoroughly per the persuasive sentence structure. Meanwhile, one Shopee advertisement does not meet the persuasive sentence structure due to its short duration. This short advertisement aims to prevent boredom and make the message conveyed to the general public easy to remember, so it can clearly target the main message directly. The five Shopee advertisements still have at least one filled structure, namely the Invitation Statement (PA), making them effective in inviting the audience